PENERAPAN PIDANA DENDA MELEBIHI ANCAMA MAKSIMUM PADA TINDAK PIDAN PENCABULAN ANAK - Petrus Zagoto (LPPM Universitas Nias Raya, 2025)
Based on the background of this problem, the problem formulation in this research is how to impose a fine that exceeds the maximum threat for the crime of child molestation (Decision Study Number 8/Pid.Sus/2021/Pn.Jap). The type of research used in this research is normative legal research using a statutory regulation approach, case approach, and analytical approach by collecting secondary data consisting of primary legal material, secondary legal material, and tertiary legal material. Qualitative data analysis, namely secondary data obtained from research results, is arranged descriptively, logically and systematically, and conclusions are drawn using inductive methods. Based on the research findings and discussion, it can be concluded that the application of a fine exceeding the maximum threat for the crime of child molestation (decision study number 8/Pid.Sus/2021/PN.Jap) is not legally justified because it does not provide a sense of justice to the defendant so that violates the principles of the rule of law where in article 82 paragraph 1 of the child protection law the penalty is limited to a fine of Rp. 60,000 Million – Rp. 300,000 Million. However, in the judge's decision, he gave a higher award, namely Rp. 800,000 million thereby violating applicable statutory provisions. The author's suggestions are; (1) Judges should be more careful in deciding cases because Indonesia is a rule of law country. (2) Imposing a sentence that is not in accordance with the rules is an indication of a violation of human rights. (3) The Supreme Court or the judicial commission as a supervisor of the performance of judges should tighten supervision of judges who give sentences to people who do not comply with the applicable laws and regulations.